Tax Avoidance, Dividend Policy, and Free Cash Flow as Determinants of Capital Structure: Evidence from Indonesian Manufacturing Firms - Wulandari, Rosita; Ali Mubarok; Syafrizal; Nurhayati, Sri Astuti; Siahaan, Frixilla Angeliq Cinta Maras; Pratama, Salsabila Dera (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2026)
This study investigates how tax avoidance, dividend policy, and free cash flow influence the capital structure of manufacturing companies listed on the Indonesia Stock Exchange over the 2017–2022 period. The research adopts a quantitative approach using panel data from 22 listed firms. Model selection testing identifies the Random Effect Model as the most suitable method for estimation. The finding indicate that tax avoidance has a positive and statistically significant impact on capital structure, firms with greater tax efficiency are more likely to increase their use debt usage to obtain tax benefits. Dividend policy also shows a positive and significant effect, indicating that firms distributing higher dividends rely more on external financing to maintain operational liquidity. In contrast, free cash flow has a negative and significant effect, suggesting that firms with strong internal cash availability prefer internal financing and reduce dependence on debt. The model explains 25.6 percent of the variation in capital structure and is statistically significant. These results align with trade off theory, pecking order theory, and agency theory in explaining corporate financing behavior. The study provides practical insights for financial managers in aligning tax planning, dividend decisions, and cash flow management with long term capital structure strategies.